New Tapeworm Lytocestus gariepinusae n. sp. from a Freshwater Fish Clarias gariepinus at Makani Dam, Dist. Osmanabad, M.S. India - Jaywant S. Dhole, Karmveer N. Kadam1* and (Recent Research in Science and Technology, 2011)
The present communication deals with description of a new species Lytocestus gariepinusae n. sp. is reported from freshwater fish Clarias gariepinus at Makani dam, Dist. Osmanabad.. It differs from all known species of the genus, with the characters like, head is short, elongated, narrow anteriorly broad posteriorly: neck wide, medium squarish: gonads situated in posterior most region of worm, testes 1375 – 1385 in number, preovarian, scattered in middle region of worm: ovary large, butterfly shaped, Vitellaria granular.